On tracking control of rigid and flexible joint robots - Loria, Antonio; Ortega, Romeo (Zielona Góra: Uniwersytet Zielonogórski)
The problem of (semi-global) trajectory tracking control of "rigid" and "flexible" joints robots using computed torque based controllers is considered. The paper contains two contributions; firstly, for rigid robots it is shown that velocity in the control algorithm can be replaced by the filtered position, thus obviating the explicit need for "state observers".
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka